MSME Assistance Through Tempe Product Branding by Opinionjo Village Purwodadi - Yuwita, Nurma; Solihah, Nikmatus; Sakdiyah, Anis Fatus (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Tempe in Parerejo Village, Purwodadi, Pasuruan, has good potential; therefore, in addition to making raw Tempe, Tempe artisans also innovate by processing it into various products, such as tempe chips and Tempe pudding. However, it is known that the problems MSMEs face in Parerejo Village, Purwodadi, are in the promotional media that could be more attractive, and there is a need for more understanding of business actors regarding branding. Community service through mentoring MSMEs aims to empower MSME actors in Parerejo Village and increase public knowledge about branding strategies. The method in this service is CBR (Community Based Research). The results of community service through this mentoring can impact the MSME community in Parerjo-Purwodadi Village by increasing Brand Awareness, building brand image, having an online MSME community, and increasing sales. After this mentoring, MSME participants gain insight into the concept of branding, which can increase product appeal and use relevant advertising techniques to reach a wider audience. Through interactive sessions and direct practice, participants learn how to brand products and utilize digital platforms, including social media.